CF3CF2N=S(F)CF3: Vibrational spectra and conformational properties - Robles, Norma Lis (2014)
The structural, conformational, and configurational properties of 1,1,1-trifluoro-N-(1,1,2,2,2-pentafluoroethyl) methanesulfinimidoyl fluoride, CF3CF2N=S(F)CF3 have been studied by vibrational spectroscopy [IR (vapor) and Raman (liquid)] and quantum chemical calculations [B3LYP, MP2 and B3PW91 levels of theory (using the 6-311+G(d) and 6-311+G(2df) basis sets). According to these theoretical approximations, CF3CF2N=S(F)CF3 might be found in the gas phase as a mixture of a favoured anticlinal form (CAN bond anticlinal with respect to the CASAF bisector angle) and a less abundant syn conformer showing C1 symmetry as well (DG 1.5 kcal mol1). However, corresponding vibrational modes for these conformers show only small shifts which would not allow confidently detecting the rather small contribution of this second form in the experimental spectra.